Behind the screen: drug discovery using the big data of phenotypic analysis - Froney, Merrill M.; Jarstfer, Michael B.; Pattenden, Samantha G.; Solem, Amanda C.; Aina, Olubunmi O.; Eslinger, Melissa R.; Thomas, Aeisha; Alexander, Courtney M. (Frontiers in Education, 2024)
Technological advances in drug discovery are exciting to students, but it is challenging for faculty to maintain the pace with these developments, particularly within undergraduate courses. In recent years, a High-throughput Discovery Science & Inquiry-based Case Studies for Today's Students (HITS) Research Coordination Network has been assembled to address the mechanism of how faculty can, on-pace, introduce these advancements. As a part of HITS, our team has developed "Behind the Screen: Drug Discovery using the Big Data of Phenotypic Analysis" to introduce students and faculty to phenotypic screening as a tool to identify inhibitors of diseases that do not have known cellular targets. This case guides faculty and students though current screening methods using statistics and can be applied at undergraduate and graduate levels.Tested across seventy students at three universities and a variety of courses, our case utilizes datasets modeled on a real phenotypic screening method as an accessible way to teach students about current methods in drug discovery. Students will learn how to identify hit compounds from a dataset they've analyzed and understand the biological significance of the results they generate. They are guided through practical statistical procedures, similar to those of researchers engaging in a novel drug discovery strategy. Student survey data demonstrated that the case was successful in improving student attitudes in their ability to discuss key topics, with both undergraduate and graduate students having a significant increase in confidence. Together, we present a case that uses big data to examine the utility of a novel phenotypic screening strategy, a pedagogical tool that can be customized for a wide variety of courses.